Performance improvement and emissions reduction of methanol fuelled marine dual-fuel engine with variable compression ratio - Panagiotis Karvounis; Gerasimos Theotokatos (Fuel Processing Technology)
Methanol use in marine engines is associated with challenges pertaining to misfiring and knocking. This study aims at parametrically optimising a marine dual-fuel four stroke engine considering variable compression ratio (VCR) settings and methanol direct injection with 90 % energy fraction. CFD models are developed and validated against experimental data. Parametric runs are employed in 20, 55 and 90 % load, with compression ratio ranging 11–19, to reveal the optimal CR values for each load considering the engine performance and emissions parameters along with constraints on combustion efficiency and stability. The sustainability index is employed to assess the environmental sustainability of the engine under optimal VCR settings compared to FCR. The results reveal that the engine thermal efficiency for CR 19, 16 and 12 at low, medium and high loads respectively increases by 7 %, 2 % at low and medium loads, whereas, decreases by 4 % at the high load. The engine with the proposed VCR settings achieves the compliance with the IMO Tier III limits and increases its sustainability index by 21 % compared to the fixed compression ratio. This study provides insights for the effective use of high methanol energy fractions in marine dual engines, thus contributing to the shipping sector sustainability.